Contemporary Costs Associated With Transcatheter Versus Surgical Aortic Valve Replacement in Medicare Beneficiaries. (23rd February 2022) - Baron, Suzanne J.; Ryan, Michael P.; Moore, Kimberly A.; Clancy, Seth J.; Gunnarsson, Candace L.
Abstract : Background: In patients with severe aortic stenosis, treatment with transcatheter aortic valve replacement (TAVR) has been shown to be cost-effective in the high-risk surgical population and cost-saving in the intermediate-risk population when compared with surgical aortic valve replacement (SAVR) in early pivotal clinical trials. Whether TAVR is associated with comparable or lower costs when compared with SAVR in contemporary clinical practice is unknown. Methods: Using data from the Medicare Dataset Standard Analytic Files 5% Fee for Service database, patients receiving either TAVR or SAVR between 2016 and 2018 were identified. Patients were categorized as low, intermediate, or high mortality risk based on 2 validated indices—the Hospital Frailty Risk Score and the logEuroScore. Health care costs out to 1 year were compared between TAVR and SAVR among the low, intermediate, and high-risk groups, after adjustment for patient demographics. Results: Nine thousand seven hundred forty-six patients were identified (4834 TAVR; 3760 SAVR) and included in the analysis. Patients receiving TAVR were older and more likely to be female. Index hospitalization costs were significantly lower with TAVR compared with SAVR across all risk strata (logEuroScore: low: $61 845 versus $68 986; intermediate: $64 658 versus $76 965; high: $65 594 versus $91 005; P <0.001 for all). Follow-up costs through 1 year were generally lower with TAVR and this difference was more pronounced in the low risk groups (logEuroScore: $9763 versus $14 073; Hospital Frailty Risk Score: $10 116 versus $12 880). Accordingly, cumulative 1-year costs were substantially lower with TAVR compared with SAVR. Conclusions: At 1 year, TAVR is associated with lower health care costs across all risk strata when compared with SAVR in contemporary practice. If long-term data continue to demonstrate similar clinical outcomes and valve durability with TAVR and SAVR, these findings suggest that TAVR may be the preferred treatment strategy for patients with aortic stenosis from an economic standpoint.